1996
DOI: 10.1200/jco.1996.14.4.1106
|View full text |Cite
|
Sign up to set email alerts
|

Short-course adjuvant chemotherapy in high-risk stage I nonseminomatous germ cell tumors of the testis: a Medical Research Council report.

Abstract: There have been only two relapses among 114 cases of high-risk stage I NSGCTT treated with two courses of adjuvant BEP chemotherapy. The 95% confidence interval (CI) excludes a true relapse rate of more than 5%. Of 104 patients confirmed on histopathology review to have GCT, there has been only one relapse. Adjuvant chemotherapy is free from significant long-term toxicity, offering an effective alternative to surveillance or retroperitoneal lymph node dissection (RPLND) followed by surveillance, and may be pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
116
0
11

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 294 publications
(131 citation statements)
references
References 18 publications
4
116
0
11
Order By: Relevance
“…This has been shown to reduce the rate of relapse to o5% (Cullen et al, 1996). The proven GCT relapses seen in this trial occurred after 7 months and were detected by raised markers, and a published review including 148 patients treated with adjuvant chemotherapy demonstrated six (4%) relapses, all within 2 years of treatment .…”
Section: Nonseminoma Stage Imentioning
confidence: 63%
“…This has been shown to reduce the rate of relapse to o5% (Cullen et al, 1996). The proven GCT relapses seen in this trial occurred after 7 months and were detected by raised markers, and a published review including 148 patients treated with adjuvant chemotherapy demonstrated six (4%) relapses, all within 2 years of treatment .…”
Section: Nonseminoma Stage Imentioning
confidence: 63%
“…Cullen et al reported on outcomes of 114 patients with high-risk stage A NSGCT who were treated with 2 courses of combined bleomycin, etoposide, and cisplatin. 10 At a median follow-up of 4 years, there were 2 recurrences, 1 at 7 months in the retroperitoneum, liver, and lung and the other at 18 months in the groin. Other series have reported similar success with longterm follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…39,48,65,[71][72][73][74][75] Because the RCT compared adjuvant chemotherapy to RPLND, only the chemotherapy arm was included in the meta-analysis. Although the follow-up times of the included studies varied, all had sufficient follow-up that almost all recurrences that would occur among these patients were included.…”
Section: Adjuvant Chemotherapymentioning
confidence: 99%